PERANCANGAN BUKU DONGENG “PARAMYTHI OF LILY AND GIANT SNAKE” BESERTA MEDIA PROMOSINYA - Surya, Tony; Sutanto, Shienny Megawati (Jurnal VICIDI, 2020)
The reason for this research is to know about fairy tale book which can take interest for consument and good for children about 4-7 years old, so it can be applied to Indonesian folklore “Paramythi of Lily and giant snake” as a media to conserve Indonesian folklore. Quantity and quality research such as observation, study literature and interview. Folk lore is a story formed between a fictional thinking and reality, to become a story line which contain the meaning of life and to interact with others. A traditional story who try to explain about the world and the legacy in local country. Folklore is a partial of culturistic and history which belongs to Indonesia. The result form the research shows that fairy tale / folklore story has started to be forgotten and considered old in this modern era. Basically, Indonesia folklore is teaching about character building or moral education and as entertainment. From the survey result, Indonesian still assume that fairy tale book is important and they like rather a fantasy tale with a cute character design in modern backgorund. Most of them like the international fairy tale rather than the local. Things that they think important in fairy tale book is the story line, then design and colour, and the last is book cover. Interactive fairy tale book is chosen as the solution the consument wanted than the common one. The reason they like international fairy tale is because the illustration design are intersting and the story line consist of great morale and easy to understand.